On Reading : From Walden - Thoreau, Henry David, 1817-1862 (Book collections on Project MUSE., 2014)
As the digital age settles on us and the ebook revolution dawns, the question of why we read to begin with is often forgotten. Who better to turn to for guidance on this question than the man who sought refuge in the simple things we often take for granted, Henry David Thoreau. His thoughts on reading are as relevant in the eBook era as they were in the age of the locomotive.